Time as a Barrier to International Trade and Economic Growth: The Role of Information and Communication Technology in Reducing Time Cost - Nashwa Mostafa Ali Mohamed (Arab Economic and Business Journal, 2015)
The study examines the relationship between reducing time and international trade. Primarily, through the role of information and communication technology, within the trade facilities, in reducing the time required for import and export, and discussing its impact on economic growth. The Two-Stages Least Squares method was used to estimate the econometric model for 16 Arab countries during the period (2005-2011). The study concluded that the information and communication technology leads to time and cost reduction, thereby increasing the value of merchandise exports and imports. In addition, there is a positive relationship between the decline in time and economic growth.